Sport Management and Research Centers: Information to Enhance the Field. Issue 4 (1st October 2020) - Seifried, Chad; Downs, Ben; Otto, Marcella; Mamo, Yoseph
Abstract: The purpose of the present review serves to provide information about the viability and utility of research centers for sport management faculty. To achieve this objective, the present paper begins with a discussion on the evolution of research centers in the United States. Second, the need for research centers in the contemporary university setting is established and the benefits of research centers to both society and science (i.e. sport management) are identified, along with existing challenges and barriers. Third, the present examination explains specific heuristic categories of research centers developed by Ikenberry and Friedman (1972 ) through the frame of leadership, resources (e.g. standard, adaptive, shadow), and relationships (e.g. university-industry, programmed/corporate alliance, for-profit spin-offs, technology transfer, etc.) that sport management faculty should understand before creating their own center. Fourth, we describe research center evaluation methods and identify general but necessary points of emphasis to develop a proposal for universities.